Impact of history of depression on 1-year outcomes in patients with chronic coronary syndromes: An analysis of a contemporary, prospective, nationwide registry. (15th May 2021) - De Luca, Leonardo; Temporelli, Pier Luigi; Amico, Antonio Francesco; Gonzini, Lucio; Uguccioni, Massimo; Varani, Elisabetta; Brunetti, Natale Daniele; Colivicchi, Furio; Gabrielli, Domenico; Gulizia, Michele Massimo
Abstract: Background: Depression is common in patients with acute cardiovascular conditions and it is associated with adverse clinical events. Methods: Using the data from a nationwide, prospective registry on patients with chronic coronary syndromes (CCS), we assessed the impact of depression on major adverse cardiovascular events (MACE), a composite of all-cause death and hospitalization for myocardial infarction, revascularization, heart failure or stroke, and quality of life (QoL) at 1-year follow-up. Results: From the 5070 consecutive CCS patients enrolled in the registry, 531 (10.5%) presented a history of depression and the remaining 4539 (89.5%) did not. At 1 year (median 369; IQR 362–378 days) from enrolment, the incidence of the primary composite outcome was 9.8% for patients with a history of depression and 7.2% for non-depressed patients ( p  = 0.03). Patients with history of depression had a significantly higher rate of all-cause mortality (3.0% vs 1.4%; p  = 0.004) and hospital admission for heart failure (3.4% vs 1.3%; p  = 0.0002) compared to the group without depression. However, history of depression did not result as an independent predictor of MACE at multivariable analysis [hazard ratio 1.17, 95% confidence interval (0.87–1.58), p  = 0.31]. Depressed patients had worse QoL according to all domains of the EQ. 5D-5L questionnaire as compared to non-depressed patients (all p  < 0.001), at both enrolment and follow-up. Conclusions: In this contemporary, large cohort of consecutive patients with CCS, patients with a history of depression experienced a two-fold rate of mortality, a higher incidence of MACE and a worse QoL at 1-year follow-up, compared to non-depressed patients. Highlights: We assessed the impact of depression on 1-year MACE among patients with chronic coronary syndromes; The incidence of MACE was significantly higher in patients with a history of depression compared to other patients; Patients with depression had a significantly higher rate of all-cause mortality and heart failure non-depressed patients; Depressed patients had a worse quality of life as compared to non-depressed patients, at both enrolment and follow-up.